The Potency of Metarhizium anisopliae in Disturbing Oryctes rhinoceros (Coleoptera: Scarabaeidae) Growth and Development - Ummi Maysaroh; Edhi Martono; Tri Harjaka (Universitas Gadjah Mada, 2022)
Metarhizium anisopliae is one of the most frequently used insect pathogen fungi in controlling Oryctes rhinoceros. This research aims to learn the potency of fungus M. anisopliae against O. rhinoceros larvae growth and development at the laboratory. The research methods used are T-tests comprising seven treatments and three replications. Fungi were applied in all larvae instar stages starting from the pre-molting of the first larvae instar, post-molting of the second larvae instar, active second larvae instar, pre-molting of the second larvae instar, post-molting of the third larvae instar, active third larvae instar, and pre-pupae stage which were then compared with each instar’s own control. The result indicates that fungus M. anisopliae is capable of suppressing O. rhinoceros growth and development. The fungus induced highest mortality rate of 87% to the third instar larvae and lowest mortality rate of 27% to the pre-molting of the first instar larvae. The fungus also affected the duration of larval stage. At pre-molting of the third larvae instar treated with M. anisopliae, the larval duration was 40 days compared to that of control that took 135 days. At the post-molting of the third larvae instar, the larval duration was 25 days compared to that of control that took 120 days. At the third larvae instar, the larval duration was no more than 15 days compared to that of control that reached 110 days. At pre-pupal stage, the larvae only lasted for 6 days while at control, they were able to last for 15 days. The fungus also affected the success of larva development in becoming pupae in all O. rhinoceros larval stage. The lowest success rate was found in the post-molting of the third larvae instar treated with M. anisopliae with 7% compared to its control with 100% while the highest success rate was found in the pre-molting of the first larval instar with 47% compared to its control with 93%.